Government intervention, market development, and pollution emission efficiency: Evidence from China - Wang, Ke-Liang; Zhao, Bin; Ding, Li-Li; Miao, Zhuang (The Science of the total environment, 2021)
The government and the market are the two main means for resource allocation, and both play important roles in economic development and environmental protection. Based on the theoretical mechanism analysis, this study empirically investigated the relationship between government intervention, market development, and China's provincial pollution emission efficiency by using the static panel OLS, system generalized method of moments (SYS-GMM), and panel threshold effect model during the period 2000–2017. The results show that the impact of government intervention on China's provincial pollution emission efficiency shows a non-linear U-shaped curve relationship, and there is a positive correlation between market development and provincial pollution emission efficiency in China. Government intervention and market development are complementary, rather than a substitute for each other, in promoting China's provincial pollution emission efficiency. When government intervention is set as the threshold variable, the impact of government intervention on China's provincial pollution emission efficiency shows the feature of “promotes first, then inhibits.” However, when market development is set as the threshold variable, government intervention is only conducive to the improvement of China's provincial pollution emission efficiency at a moderate marketization level. Lastly, some policy implications related to the government and the market in enhancing China's provincial pollution emission efficiency are presented. [Display omitted] •The relationship between government intervention, market development and pollution emission efficiency is investigated from both theoretical and empirical perspectives.•Government intervention and market development are complementary in promoting China’s provincial pollution emission efficiency.•Panel threshold effect model is employed to explore the joint impact of government intervention, market development on China’s provincial pollution emission efficiency.